The Embedding of Sports Social Organizations in Rural Governance Based on the Collaborative Governance Model of Multiple Subjects - Yu, Yanglu; Gao, Kuiting (Mathematical problems in engineering, 2022)
Rural governance is an important part of national governance, and the participation of social organizations is also very important. This research explores the multiple relationships between rural governance subjects and governance methods through the basic requirements of “co-construction and sharing” of multi-governance and the status quo of creation activities, integrates an innovative rural community governance evaluation and supervision system, and builds rural community governance evaluation and supervision system mechanism. Mutually exclusive constraints on the diversity of governance subjects will provide strategic guidance for sports social organizations to participate in diversified management.